2010
DOI: 10.1080/87568225.2010.509219
|View full text |Cite
|
Sign up to set email alerts
|

The Counseling Center: An Undervalued Resource in Recruitment, Retention, and Risk Management

Abstract: A primary responsibility for directors of college and university counseling centers is to explain to various audiences the multiple ways such units are of value to their institutions. This article reviews the history of how counseling center directors have been encouraged to develop and describe the work of their centers. Often overlooked are the contributions that counseling centers make to institutional recruitment, retention, and risk-management activities. Research that demonstrates the relationship betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 20 publications
1
29
0
Order By: Relevance
“…In addition, higher PSP had a significant positive impact on the recommending the university beyond demographics, client perceptions and wait measures. This reinforces that a UCC can help with prospective student recruitment (Bishop, 2010), and be a positive source for public relations for a university (Blau et al, 2015;Brunner et al, 2014).…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…In addition, higher PSP had a significant positive impact on the recommending the university beyond demographics, client perceptions and wait measures. This reinforces that a UCC can help with prospective student recruitment (Bishop, 2010), and be a positive source for public relations for a university (Blau et al, 2015;Brunner et al, 2014).…”
Section: Discussionmentioning
confidence: 91%
“…Bielen and Demoulin (2007) found that higher patient satisfaction led to a higher likelihood of recommending the radiological services to relatives. Bishop (2010) noted that UCCs may positively contribute to the general recruitment of prospective students. UCC clients who have higher PSP may be more likely to recommend their university to others.…”
Section: Ucc Psp Related To Recommending a Universitymentioning
confidence: 99%
See 1 more Smart Citation
“…Scientifically demonstrating to University administration that the on-campus UCC site can help undergraduates in distress should ideally help the UCC to increase its allocation of university-based resources (Bishop, 2010;Hunt et al, 2012). Such research efforts need to be continued as UCCs compete with other university stakeholders for resources (Castonguay, Locke, & Hayes, 2011).…”
Section: Implications For Practicing College Clinicians and Resourcinmentioning
confidence: 99%
“…Scientifically demonstrating to higher-level University administration that a UCC can help undergraduates in distress should ideally help the UCC to increase its allocation of university-based resources (Bishop, 2010;Hunt et al, 2012). Linking student services to student life satisfaction can be important for improving the overall financial health of an institution.…”
Section: Implications For Practicing College Clinicians and Resourcinmentioning
confidence: 99%